Bottom ash in concrete - Muftah, Fadhluhartini; Mohd Sani, Mohd Syahrul Hisyam; Muda, Zulkifli (University Teknology MARA Pahang, 2011)
From the coal generating system, the waste materials that produced are the bottom ash and fly ash. Bottom ash is collected at the bottom of boiler or furnace and sometimes it is placed on the surface of the chamber in a water-filled hopper. High-pressure water is used to remove the bottom ash from the chamber. Fly ash is disposed to atmosphere by tall chimney. 80% of the product of electric coal power plant will become fly ash and the remaining 20% is bottom ash. The bottom ash is physically coarse, porous, light. glassy. granular. greyish and incombustible materials which are suitable to be used in concrete jar civil engineering application. The type and properties of bottom ash produced depend on the type of boiler or furnace and also the sources of raw coal. With the chemical analysis and physical testing, the bottom ash shows unique properties that can be applied in concrete. Many researchers discovered that the bottom ash can be functioning as a material in producing various types of concrete material, new concrete technology, masonry engineering and also highway engineering application